The serum interleukin-6 levels in the early postoperative period after surgical castration – the influence of ERT - Woźniakowska, Ewa; Donica, Helena; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Background. The role of inflamation in the pathogenesis of cardiovascular disease (CVD) has been well established. Measurement of the proinflamatory cytokines such as interleukin-6 (IL-6) has been recommended for determining the risk of CVD. Women with surgical menopause (due to biletaral salpingo-oophorectomy) are susceptible to vascular complications related to thrombogenesis and atherogenesis. Estradiol deficiency promotes bone loss through increasing interleukin-6 activity. Purpose of the study. The aim of our study was to evaluate the impact of surgical menopause on serum Il-6 concentration including the effect of early initiated estrogen replacement therapy (ERT). Material and methods. Twenty five premenopausal women (mean age 49±2,6 years) undergoing total abdominal hysterectomy with bilateral oophorectomy (TAH&BSO) were studied. IL-6 concentrations were measured in venous blood serum by means of ELISA assay in three time points: before the operation, in the postoperative day 2 and in postoperative day 3 (24 hours after starting ERT in the form of transdermal 17b -estradiol - 100 mg/24h; Estraderm TTS 100, Novartis). Results. In the postoperative day 2 a highly statistically significant (p < 0.001) increase in IL-6 levels was observed as compared to preoperative values. In the 3rd postoperative day, twenty four hours after the initiation of ERT, a strongly significant (p<0.001) decrease in IL-6 concentration was observed as compared to postoperative day-2 levels. Conclusions. Surgical castration results in the immediate, almost 8-fold increase in IL-6 level. Early initiation of ERT after TAH&BSO decreases the IL-6 concentration after 24 hours of estrogen supplementation which may have both cardioprotective and osteoprotective consequences.